2018
DOI: 10.1111/jcmm.13859
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of proliferation and invasion by the IGF signalling pathway in Epstein‐Barr virus‐positive gastric cancer

Abstract: Several carcinomas including gastric cancer have been reported to contain Epstein‐Barr virus (EBV) infection. EBV‐associated gastric cancer (EBVaGC) is classified as one of four molecular subtypes of gastric cancer by The Cancer Genome Atlas (TCGA) group with increased immune‐related signatures. Identification of EBV‐dependent pathways with significant biological roles is needed for EBVaGC. To compare the biological changes between AGS gastric epithelial cells and EBV‐infected AGS (AGS‐EBV) cells, proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the present study, we used an EBVaGC in vitro model to discover metabolic alterations in GC caused by EBV infection, which we accomplished through omics-based profiling at the metabolic level, followed by statistical and pathway analyses. To mimic the infection of EBV in GC, we adopted a well-established EBVaGC in vitro model from a previous study that had validated the success of EBV infection in a typical GC cell line through biological methods [34]. We also validated the model using real-time RT-PCR for the EBNA-1 EBV antigen (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used an EBVaGC in vitro model to discover metabolic alterations in GC caused by EBV infection, which we accomplished through omics-based profiling at the metabolic level, followed by statistical and pathway analyses. To mimic the infection of EBV in GC, we adopted a well-established EBVaGC in vitro model from a previous study that had validated the success of EBV infection in a typical GC cell line through biological methods [34]. We also validated the model using real-time RT-PCR for the EBNA-1 EBV antigen (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment results for these 107 genes revealed that many of them are involved in cell proliferation pathway such as E2F Targets, Myc Targets, Mitotic Spindle, and G2-M Checkpoint. The investigations have shown that AGS cell lines infected by EBV exhibit reduced growth and migration capabilities compared to the control group [ 25 ]. Moreover, it has been demonstrated that certain microRNAs generated by EBV, such as miR-BART12, can target crucial genes involved in cellular proliferation and migration pathways [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that certain microRNAs generated by EBV, such as miR-BART12, can target crucial genes involved in cellular proliferation and migration pathways [ 26 ]. It has been demonstrated that AGS cells infected with EBV exhibit a significantly reduced rate of cellular proliferation compared to non-infected cells [ 25 ]. On the other hand, our results showed that the increased expression of some genes, such as NT5DC2, KDELC1, LRFN1, HRNR, TET1 , and ABCB5 in GC is associated with a poor prognosis for patients, while the expression of the mentioned genes could be reduced by EBV.…”
Section: Discussionmentioning
confidence: 99%